KARAKTERISTIK JIWA BERWIRAUSAHA MAHASISWA PROGRAM STUDI TEKNOLOGI PENGOLAHAN PRODUK KULIT POLITEKNIK ATK YOGYAKARTA - Nurwantoro; Wawan Budi Setyawan (Politeknik ATK Yogyakarta, 2018)
This study was conducted to determine the characteristics of entrepreneurial of the TPPK Study Program students in Polytechnic ATK Yogyakarta. Variables observed consisted of the entrepreneurial personality traits include self confidence, attitude towards risk, creative and innovative, discipline and hard works, future oriented, curious know how, and honest and independent. The analytical method used was descriptive qualitative. The results showed that of the 7 characteristics of the entrepreneurial spirit that became the research variable the characteristics of having self-confidence, being able to take risks, being future-oriented, having curiosity, honesty and being independent showed high interest while creative and innovative, disciplined and hard work showing moderate results. Other results of this study indicated that the percentage of ATK Yogyakarta Polytechnic students who had aspirations for independent business (entrepreneurs) is 74.49%. The remaining 25.51% had aspirations as employees, both private and civil servants.